Metaphorical competence in multilingual context of language acquisition and learning - Batoréo, Hanna (2020)
It has been defended since Gibbs (1994) that in proper contexts people mostly use the metaphorical asset of a message rather than its literal meaning, which means that in a proper communicative context we express ourselves metaphorically and that metaphors are features of communicative interaction. In the present paper we discuss the notion of metaphorical competence (Aleshtar & Dowlatabadi 2014: 1895) in the process of multilingual acquisition and learning. This competence goes beyond other competences, such as communicative or linguistic, a speaker has to master when (s)he wants to speak a new non-native language. Thus, the importance of metaphorical competence implies that a speaker should not only be linguistically and communicatively appropriate but also conceptually appropriate. Based on previous studies by Sinha and Jansen (2004), Kövecses (2005), Palmer & Sharifian (2007), Gibbs & Colston (2012) and Sharifian (2015), among others, we defend that research in the area should be centred not exclusively on Language but on interaction in a triangle Cognition – Language – Culture. This interaction is embodied, which means the way we conceptualise the world is based on body and bodily experience mediated by culture, giving origin to physiological and/or cultural embodiment. In this study we present research from different language backgrounds both from occidental cultures (giving examples from European Portuguese, English and Polish) and oriental ones (Mandarin Chinese). We centre our analysis on conceptualization of emotions (for instance, manifested in the case of emotional expression of feeling hungry) and moral values (such as courage). This implies both physiological and cultural embodiment, giving evidence of differences that can be observed in mapping of different organs – such as heart or gallbladder – in different cultures into different emotions and values (cf. Yu 2003, 2007, 2009; Batoréo 2017a, b & c). We defend that in a multilingual context conceptual appropriateness in metaphorical competence and metaphor awareness play a fundamental role in the acquisition of figurative language (cf. Doiz & Elizari 2013). Figurative language is understood to be (at least, partially) motivated, and thus object of (partially) insightful learning (cf. Boers 2001, Boers et al. 2004, 2007).